An exploratory study of children’s expressive language productivity in relation to teachers’ use of communication-supporting strategies - Edlund, Karin; Kjellmer, Liselotte; Hemmingsson, Helena; Berglund, Eva (Frontiers in Education, 2024)
Supporting children’s language development, particularly oral language, is crucial as it constitutes the basis for the further development of literacy skills. This study explored patterns of primary school children’s expressive language productivity over time in relation to a professional development (PD) program designed to further teachers’ use of communication-supporting strategies to promote child talk. Framed by a Tier 2 response to intervention model, teacher-child verbal interactions were observed during structured small-group conversations. The participants were 36 children (M age 8;2 years old), with and without speech, language and communication needs (SLCN) attending three mainstream classes in two Swedish municipalities. Two teachers followed a 10-week PD program, and a third teacher participated for comparison purposes. We measured the children’s expressive language productivity in relation to the teachers’ strategy use pre-intervention, post-intervention, and at a two-month follow-up. In the results, we found a tendency that when the teachers used the strategies frequently, the children’s expressive language productivity seemed suppressed. Although the results showed a large variation in the children’s expressive language productivity, a tentative conclusion is that the children with SLCN may also be stimulated and willing to participate verbally during this type of small-group conversation. This finding suggests support for an inclusive Tier 2 approach of mixed groups with both children with and without SLCN. Based on our findings, we also suggest stressing in the PD program the need for teachers to balance their strategy use in the interactions with the children to provide ample opportunities for the children to talk and express themselves.